Knowledge, attitudes, and practices towards COVID-19 among residents of Gujarat, India - Domadia, Dharmesh; Patadiya, Jigisha; Bhabhor, Prakash (International Journal of Basic & Clinical Pharmacology, 2021)
Background: India, having diverse demographic profile, any single measure to curtain COVID-19 spread will become ineffective by default. Hence, determining knowledge and behaviours of population regarding COVID-19 is must to extract and decide on an effective approach to reduce the spread of COVID-19. For the same, we conducted KAP study. Methods: It was a KAP study of adult residents of various districts of Gujarat, India; consisting questions with multiple responses pertaining to knowledge, attitude, and practices towards COVID-19. Responses were analysed and represented by their percentage. Knowledge related questions’ responses were statistically analysed based upon responder’s age, gender, education level. Results: Knowledge scores of male and female participants were 7.03 and 6.96. Mean knowledge score of age group of 18-30 years, differed significantly to that of age group of >60 years. Study participants’ scores didn’t differ statistically according their education levels. 91.3% participants felt that COVID-19 can be more effectively managed if person has been diagnosed or tested earlier in the disease. 69.8% participants felt that patients of COVID-19 infection can be safely treated at home. 74.4% of participant were in favour of lockdown if need arises. 77% participants were willing to take COVID-19 vaccine. Conclusions: Knowledge level didn’t differ for any gender or education level. Knowledge scores of populations above age of 60 years were statistically less as compared to the scores of participants aged between 18 to 30 years. TV news channels and newspapers were most sought way of getting information for current study population.